2002
DOI: 10.1104/pp.000919
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Lipoxygenase-Independent Senescence Mechanism in Alstroemeria peruviana Floral Tissue

Abstract: The role of lipoxygenase (lox) in senescence of Alstroemeria peruviana flowers was investigated using a combination of in vitro assays and chemical profiling of the lipid oxidation products generated. Phospholipids and galactolipids were extensively degraded during senescence in both sepals and petals and the ratio of saturated/unsaturated fatty acids increased. Lox protein levels and enzymatic activity declined markedly after flower opening. Stereochemical analysis of lox products showed that 13-lox was the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 51 publications
5
34
0
Order By: Relevance
“…Although the role of LOX in Chl degradation in vivo is still controversial (Takamiya et al 2000), some studies have reported that Chl degradation is coupled with the oxidation of unsaturated fatty acids by LOX (Jaren-Galan et al 1999). In petal senescence in Alstroemeria peruviana and postharvest storage of broccoli, a decrease in LOX activity is associated with Chl loss (Zhuang et al 1997, Leverentz et al 2002. The similar results in our study support this relationship between LOX activity and Chl degradation.…”
Section: ⎯⎯⎯⎯supporting
confidence: 91%
“…Although the role of LOX in Chl degradation in vivo is still controversial (Takamiya et al 2000), some studies have reported that Chl degradation is coupled with the oxidation of unsaturated fatty acids by LOX (Jaren-Galan et al 1999). In petal senescence in Alstroemeria peruviana and postharvest storage of broccoli, a decrease in LOX activity is associated with Chl loss (Zhuang et al 1997, Leverentz et al 2002. The similar results in our study support this relationship between LOX activity and Chl degradation.…”
Section: ⎯⎯⎯⎯supporting
confidence: 91%
“…Membrane polyunsaturated fatty acids are prone to oxidation either by enzymatic means (LOX) or through autoxidative events (non-enzyme catalyzed). Increases in lipid peroxidation, usually determind from changes in MDA concentration, accompanies the increase in LOX activity while the products of peroxidation are considered to perturb membrane function (Leverentz et al 2002). It has already been reported that LOX activity may promote senescence through oxidative damage membrane as seen in day lily (Panavas and Rubinstein 1998) and gladiolus (Peary and Prince 1990;Hossain et al 2006).…”
Section: Resultsmentioning
confidence: 95%
“…Large reductions in total protein content typically occur in senescing organs (Buchanan-Wollaston et al 2003, Hensel et al 1993) and may reflect a lack of synthesis or increased protein catabolism in flavedo with reduced ATP content after CMNP treatment (Alferez et al 2005). Increased electrolyte leakage was an early event induced by CMNP, indicating a loss of membrane semipermeability and onset of senescence (Leverentz et al 2002, Thompson et al 1998 caused by the substituted pyrazole. AT treatment was unable to arrest CMNP-induced electrolytic leakage.…”
Section: Discussionmentioning
confidence: 99%